The impact of plasma 25‐hydroxyvitamin D on pulmonary function and exercise physiology in cystic fibrosis: A multicentre retrospective study. Issue 2 (1st June 2021) - Revuelta Iniesta, Raquel; Causer, Adam J.; Arregui‐Fresneda, Irantzu; Connett, Gary; Allenby, Mark I.; Daniels, Thomas; Carroll, Mary P.; Urquhart, Don S.; Saynor, Zoe L.
Abstract: Background: A 25‐hydroxyvitamin D (25OHD) may exert immunomodulatory effects on respiratory health, which may translate to improvements in exercise physiology. Thus, we aimed to investigate whether plasma 25OHD is associated with lung function and aerobic fitness in people with cystic fibrosis (pwCF). Methods: A multicentre retrospective review of pwCF (> 9 years old) attending the Royal Hospital for Sick Children (Edinburgh) or Wessex CF‐Unit (Southampton) was performed between July 2017 and October 2019. Demographic and clinical data were collected. Plasma 25OHD measured closest in time to clinical cardiopulmonary exercise testing and/or spirometry [forced expiratory volume (FEV1 )% predicted] was recorded. Pancreatic insufficiency was diagnosed based on faecal elastase of < 100 µg g −1 . We performed multiple‐regression analysis with aerobic fitness outcomes [peak oxygen uptake (VO2 peak )] and FEV1 % predicted as primary outcomes. Results: Ninety pwCF [mean ± SD age: 19.1 ± 8.6 years, 54 (60%) children, 48 (53%) males and 88 (98%) Caucasian] were included. 25OHD deficiency and insufficiency was 15 (17%) and 44 (49%), respectively. 25OHD deficiency and insufficiency was significantly associated with pancreatic insufficiency (χ 2  = 4.8, p  = 0.02). Plasma 25OHD was not significantly associated with FEV1 % predicted ( r 2  = 0.06, p  = 0.42, 95% CI = −0.09 to 0.19) or VO2 peak ( r 2  = 0.04, p  = 0.07, 95% CI = −011 to 0.005) in all pwCF. However, 25OHD was significantly associated with both FEV1 % ( r 2  = 0.15, p  = 0.02, 95% CI = 1.99–2.64) and VO2 peak ( r 2  = 0.13, p  = 0.05, 95% CI = −0.26 to −0.005) in the paediatric cohort. Conclusions: We showed that 25OHD is associated with improved lung function and aerobic fitness in children and adolescents with CF. Mechanistic and high‐quality prospective studies including both lung function and aerobic fitness as primary outcomes are now warranted. Abstract : This study shows that there is a high prevalence of plasma 25‐hydroxyvitamin D (25OHD) deficiency and insufficiency, and highlights that despite appropriate vitamin D supplementation, total plasma 25OHD was lower in adults than in children, in those with pancreatic insufficiency and there was no seasonal variation. Plasma 25OHD abnormalities were associated with aerobic fitness and ventilatory dysfunction in people with Cystic Fibrosis (pwCF) and lower plasma 25OHD maybe associated with poorer lung function and maximal aerobic fitness in children with CF. We recommend vitamin D supplementation in all pwCF as per guidelines and that plasma 25OHD concentration is measured on the same day (or within 15 days) as cardiopulmonary exercise testing and spirometry.